Social Media in Social Organization - Aykurt, Aylin Yildirim; Sesen, Elif (European Scientific Journal, ESJ, 2017)
As global integration process creates changes and new problem areas around individuals, people try to apply new ways for resilience. One of the methods used in this frame is social organization. Also, one of the most important tools of social organization in today’s world is social media which emerge as a result of new communication technologies. The aim of this study is to reveal the role of social media in organizing society. In this context, social organization and social media were primarily defined. Some examples of the use of social media in social action and social organization have been emphasized. Data for the study was collected by using an online questionnaire. Research population of the study was Facebook users in Turkey. The sample of the study uses the convenience incidental sampling. The opinions about the role of social media in the social organization of Facebook users were examined. According to the results of the study, 72% of the participants agree that social media is a powerful tool in organizing social actions. 40% of the respondents think that social media contributes in strengthening democracy. It might be said that participants believe in the power of social media, but they never thought that this power will remain permanent.